2022
DOI: 10.1186/s12903-022-02172-8
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between skeletal bone mineral density and subjective masticatory difficulty

Abstract: Background Masticatory ability is an essential factor for sustaining quality of life and social and systemic well-being, particularly in elderly. This study aimed to reveal the association between subjective masticatory difficulty and skeletal bone mineral density (BMD). Methods Data from the Korean National Health and Nutrition Examination Survey, which was conducted from 2008 to 2011 were analyzed. This study included 13,092 Koreans (5656 males, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, higher soy protein intake in rats resulted in increased bone mineral density (BMD) under nonenergy deficiency [ 87 ]. Increased BMD may be an indicator of good oral health status in humans [ 88 , 89 ].…”
Section: Factors Affecting Optimal Dietary Intake In Older Adultsmentioning
confidence: 99%
“…Furthermore, higher soy protein intake in rats resulted in increased bone mineral density (BMD) under nonenergy deficiency [ 87 ]. Increased BMD may be an indicator of good oral health status in humans [ 88 , 89 ].…”
Section: Factors Affecting Optimal Dietary Intake In Older Adultsmentioning
confidence: 99%
“…Many efforts have been attempted to determine the risk factors for falls and fractures. Previous studies have demonstrated the strong relationships among oral health-related factors, the incidence of falls, amount of skeletal muscle mass, frailty, skeletal BMD, physical performance, and mortality rate in the elderly population 5 22 , 27 . Even though, the fragmentary associations between those factors have been reported previously, the integrated knowledge of interactions among the above factors has not been thoroughly discussed.…”
Section: Discussionmentioning
confidence: 99%
“…Oral health condition, bone mineral density (BMD), skeletal muscle mass, and frailty seem to be strongly interconnected 5 22 . The decreased number of teeth has been shown to have significant correlations with the amount of skeletal muscle mass, handgrip strength, and gait speed in the elderly 8 , 10 , 17 , 19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation